Clinical judgement and decision-making : in nursing and interprofessional healthcare - Standing, Mooi (Electronic resource, 2010)
Covering core judgement and decision making skills, this book includes contributions and case studies from a range of fields including intensive care, midwifery, and community setting and a mental health unit. It also discusses creative thinking for whole systems working, advance practice and developing skills.